The utilization of digital technology and the internet of things (IoT) in the era of the industrial revolution 4.0 - Talitha Wenifrida Massenga; Agri Adriel Bororing (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The rapid advancement of digital technology and the Internet of Things (IoT) presents significant opportunities to enhance sustainable agricultural productivity. However, the integration of these technologies in agriculture faces challenges that remain insufficiently explored. This study aims to examine the role of digital technology and IoT in enhancing sustainable agricultural productivity, identifying both the benefits and challenges associated with their application. Using a qualitative literature review approach, the study analyzes peer-reviewed articles focusing on precision farming, soil sensors, and smart irrigation systems. Findings reveal that while digital technologies and IoT can substantially increase efficiency and productivity, barriers such as limited infrastructure, high implementation costs, and data privacy concerns hinder widespread adoption. The novelty of this study lies in its holistic approach, addressing not only the potential benefits but also the practical challenges of integrating these technologies into sustainable agriculture. The study provides significant insights for agricultural practitioners, policymakers, and technology developers, offering practical recommendations to overcome existing barriers and ensure the effective adoption of these innovations to drive sustainable agricultural development.